2013
DOI: 10.1103/physreva.88.023415
|View full text |Cite
|
Sign up to set email alerts
|

Local dynamics in high-order-harmonic generation using Bohmian trajectories

Abstract: We investigate high-order harmonic generation from a Bohmian-mechanical perspective, and find that the innermost part of the core, represented by a single Bohmian trajectory, leads to the main contributions to the high-harmonic spectra. Using time-frequency analysis, we associate this central Bohmian trajectory to an ensemble of unbound classical trajectories leaving and returning to the core, in agreement with the three step model. In the Bohmian scenario, this physical picture builds up non-locally near the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
0
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(45 citation statements)
references
References 60 publications
(64 reference statements)
3
40
0
2
Order By: Relevance
“…4(b). This has been confirmed by more in-depth studies with long-range and short-range potentials but also have assessed that outer trajectories affect nonlocally the central ones [90,91].…”
Section: Intense Light-matter Interactionmentioning
confidence: 48%
“…4(b). This has been confirmed by more in-depth studies with long-range and short-range potentials but also have assessed that outer trajectories affect nonlocally the central ones [90,91].…”
Section: Intense Light-matter Interactionmentioning
confidence: 48%
“…Possible reasons are that the initial electronic wave packet in the TDSE has an initial momentum and position spread, while all CQSFA orbits are located at the tunnel exit. The initial spread of the electronic wave packet has been shown to be necessary for a good quantitative agreement with the TDSE in the context of high-order harmonic generation (HHG) [53][54][55][56]. This initial spread seems to be very important for strong-field ionization as well, as recent phase-space studies revealed that orbit-based methods that incorporate this spread exhibit a nearly quantitative agreement with the TDSE, even if tunnel ionization is not properly accounted for [57].…”
Section: Resultsmentioning
confidence: 99%
“…This may be due to the initial momentum and position spread that exists for the TDSE, but is absent for the CQSFA. In fact, recent studies on HHG [53][54][55][56] and strong-field ionization [57] indicate that this spread is necessary for a quantitative agreement with the TDSE.…”
Section: Discussionmentioning
confidence: 99%
“…Similar oscillations have also been identified and discussed in previous publications using TDSE computations [58] and the HK propagator [59] for cases where an initial wavepacket starts far from the core, and have been associated with the interference between different types of electron trajectories. The oscillations have also been studied in a different context, namely the adiabatic approximation [60,61] and Bohmian trajectories [62,63].…”
Section: Resultsmentioning
confidence: 99%